Pelatihan Peer Counselor Berbasis Virtual Reality (VR) Sebagai Upaya Pengembangan Sekolah Aman di SMP Negeri 21 Surakarta - Diani Izzatul Islam; Ardiva Walidatul Ma’rifah; Azizah Nur Istiqomah; Devina Lu’lu’ Ulayya; Eka Safitri Nuraini; Iin Fathonah Fatmalasari; Arifah Wulandari (LPPM UNIVERSITAS NAHDLATUL WATHAN MATARAM, 2026)
Bullying, violence, and sexual harassment still frequently occur in schools, but many students are reluctant to report them for fear of stigma. This initiative developed a Virtual Reality (VR)-based peer counselor training program at SMP Negeri 21 Surakarta using a blended training approach centered on experiential learning, which combined in-person sessions and VR simulations over four days, covering topics such as bullying, violence, sexual harassment, and basic peer counseling skills. Pretest-posttest evaluation results showed an increase in participants’ understanding across all measured aspects, particularly in distinguishing bullying from ordinary conflicts and understanding the role of a peer counselor. This training proved effective in enhancing participants’ knowledge, skills, and readiness as peer counselors, while also supporting the creation of a safer school environment.